PSV-16 Assessment of oxidative stress and muscle damage in exercising horses in response to level and form of vitamin E. (7th December 2018) - Fagan, M; Pazdro, R; Call, J; Abrams, A; Krotky, A; Harris, P; Duberstein, K
Abstract: Vitamin E is an essential antioxidant abundant in fresh forage and is a key component to equine diets. Most notable for its role in stopping free radical chain reactions, it is thought that supplemental vitamin E may be beneficial to athletes in reducing oxidative stress. Vitamin E has multiple chemical structures of which RRR-α-tocopherol is the most readily absorbed. Supplements can be derived from natural sources (100% RRR-α-tocopherol) or manufactured as synthetic vitamin E (12.5% RRR-α-tocopherol). This study aimed to (1) determine if supplemental vitamin E above NRC recommendations is beneficial to exercising horses and (2) determine if there is a benefit of natural compared to synthetic vitamin E. After a 2-week washout, 18 horses were divided into three groups and fed a control diet plus: (1) 1000 IU synthetic α-tocopherol acetate/d (SYN-L), or (2) 4000 IU/d synthetic α-tocopherol acetate (SYN-H), or (3) 4000 IU/d micellized RRR-α-tocopherol (NAT-H). After a 7-day acclimation period, horses began a 6-week exercise protocol of increasing intensity, with standard exercise tests (SET) performed prior to and at the conclusion of the 6-week exercise protocol. Resting, pre-feeding venous blood samples were collected at day 0 and 29. Additionally, blood samples were collected pre and 2hours post each SET plus 24hours post SET2. No differences were seen between treatment groups in serum α-tocopherol concentrations (SAT) at initial and pre SET1 times. At all other time points, NAT-H horses had higher SAT (P<0.05). Plasma malondialdehyde concentrations were lower in NAT-H vs SYN-L horses 2hours post SET2 (P=0.02). Serum aspartate aminotransferase (AST) was significantly lower 2hours post SET2 in NAT-H horses vs SYN-L or SYN-H (P<0.05). In conclusion, feeding high levels of the more bioavailable natural vitamin E source did appear to have a beneficial effect on increasing SAT and potentially reducing oxidative stress and muscle damage.